Prevalence and Incidence of Liver Dysfunction and Assessment of Biomarkers of Liver Disease in HIV-Infected Asian Children. Issue 6 (June 2015) - Aurpibul, Linda; Bunupuradah, Torsak; Sophan, Sam; Boettiger, David; Wati, Dewi K.; Nguyen, Lam V.; Saphonn, Vonthanak; Hansudewechakul, Rawiwan; Chokephaibulkit, Kulkanya; Lumbiganon, Pagakrong; Truong, Khanh H.; Do, Viet C.; et al.
Abstract : Background: We determined the prevalence and incidence of liver dysfunction before and after initiation of combination antiretroviral therapy (cART) in the TREAT Asia Pediatric HIV Observational Database. Methods: Data from children initiated on cART between 2 and 18 years of age with baseline alanine aminotransferase (ALT) available before and at least once after cART initiation in TREAT Asia Pediatric HIV Observational Database between 2008 and 2012 were analyzed. Prevalence and incidence of liver dysfunction and biomarkers including the aspartate aminotransferase to platelet ratio index and FIB4 index (a noninvasive panel to stage liver disease) were assessed. Results: Data from 1930 children were included. Their median age was 6.9 years; 49% were male; 98% were perinatally infected and 94% were initiated on non-nucleoside reverse transcriptase-based cART regimens. Before cART, the prevalence of ALT ≥3 times the upper limit of normal (×ULN) was 5.8%. There were 8.5% of children with aspartate aminotransferase to platelet ratio index >1.5 (suggestive of liver fibrosis) and 2.7% with FIB4 index >1.3 (predictive of possible cirrhosis). Among the 1143 cases with normal baseline ALT (⩽1×ULN), the incidence of ALT 3×ULN after cART was 1.19 of 1000 person-months (95% confidence interval: 0.93–1.51). Two of 350 with available tests (0.6%) met Hy's law (ALT >3×ULN and total bilirubin >2×ULN). By multivariate analysis, baseline hemoglobin <7.5 g/dL was a predictor of ALT >3×ULN, whereas age 5–9 years at cART initiation was protective for liver dysfunction. Conclusions: We demonstrated a low prevalence and incidence of liver dysfunction before and after cART initiation in children with normal baseline chemistries. In this population facing life-long cART, prospective surveillance for emergence of liver disease is warranted.